SIMULASI PENSTABILAN KADAR TAWAS PADA PENGOLAHAN AIR PDAM KOTA SEMARANG DENGAN METODE EULER - Chakim, Muhamad Nur; Rochmad, Rochmad; Arifudin, Riza (Universitas Negeri Semarang, 2015)
To the purpose research is determine solution to optimize water processing with controls chart as tool of observation and Euler method to substance dissolution on that case so acquired maximum gain. Observational method that is utilized is case study. Data that is taken is pH and muddiness of water. Hereafter been done analisis data by use of chart controls statistika to conduct quality and euler method on that case so acquired maximum water processing. From analisis extrapolation that did by controls chart to utilize program Visual Basic on pH's data is gotten xbar = 228,49, Rbar= 10,6, LKA = 7,94,xdoublebar = 7,62 and LKB = 7,29. On pH's graph has no dot out of the sphere LKA and LKB, therefore said by means controlled process its pH's quality uninfluenced by a cause. Meanwhile on muddiness data is gotten xbar = 6820,56,Rbar = 23048, LKA = 513,572 and = 227,35 and LKB = 0. On muddiness graph exists dots out of the sphere LKA and LKB as dot 1, 9, 15, and 17, therefore said by process is not controlled by its mean muddiness quality regarded by a cause. Taking conclusion from chart's purpose controls this with action issues quality cause that took in by outboard dot controls its mean take a decision production will be discontinued at the moment that condition.